Od segregacji do równych praw – z perspektywy zmian polityki edukacyjnej w aspekcie dostępu dzieci i młodzieży z niepełnosprawnością do edukacji - Serafin, Teresa (Wydawnictwo Naukowe UAM, 2015)
The article discusses the different views on people with disabilities in selected periods of history and the impact of international law on the changed perception of students with disabilities in the Polish educational system. Part 2 presents three possible paths of education of students with disabilities: segregation, integration and inclusion.
From Segregation to Equal Rights – From the Perspective of Educational Policy Changes in the Access to Education of Children and Young People with Disabilities
Keywords: segregation; integration; inclusion; evolution of views; education system; pupil/ person with a disability